Cognitive functioning in bilateral perisylvian polymicrogyria (BPP): clinical and radiological correlations. - Jansen, A; Leonard, G; Bastos, A; Esposito-Festen, J; Tampieri, D; Watkins, K; Andermann, F; Andermann, E (2005)
Bilateral perisylvian polymicrogyria (BPP) is a malformation of cortical development, frequently associated with severe dysarthria or anarthria. BPP patients are therefore often labeled as severely retarded, but a detailed neuropsychological profile has not been reported to date. In a series of 14 patients, we demonstrated that only a minority had extremely low intelligence, and that some aspects of cognitive function correlated with the extent of the cortical disorganization. Early age at seizure onset correlated positively with Performance IQ scores (P<0.05) and negatively with the extent of the lesion (P<0.01), reflecting that patients with more severe BPP are more likely to have early seizure onset, resulting in greater interference with ongoing cognitive development. Receptive and expressive language skills were found to be equally poor. Frontal lobe function and memory abilities were relatively well preserved, suggesting that the observed cognitive profiles were related, at least in part, to specific areas of cortical dysfunction and not only to global dysfunction.